Socialization of Organic and Non-Organic Waste Segregation to Minimize the Spread of Dengue Fever in Sekarjoho Prigen Village: Sosialisasi Pemilahan Sampah Organik Dan Non Organik Guna Meminimalisir Penyebaran Dbd Di Desa Sekarjoho Prigen - Faishol F, Ahmad; Febrina, Ajeng Diah Ayu; Pamungkas, Rizki Ragil; Rosah, Sinta Yanwar (Procedia of Social Sciences and Humanities, 2022)
Indonesia is the fourth largest country in the world with a population of 277 million. With a large population, it is certain that Indonesia has problems in each region, one of which is the problem of maintaining a healthy body. With this research, the author is expected to be able to provide information for readers to maintain body health by sorting organic and non-organic waste in minimizing the transmission of dengue fever in Sekarjoho Village, Prgien District. The author uses quantitative research methods to obtain relevant and accurate information. Keywords: organic and non-organic waste, DHF